Les vitraux de l’École de Pharmacie de Paris - Françoise Gatouillat (In Situ)
Built from 1877 to 1882 by Charles-Jean Laisné, the main façade of the École de Pharmacie opens onto the Avenue de l’Observatoire (Paris, 6th arr.). The new school was richly decorated with sculpture, wall-painting and stained-glass. According to the architect’s wishes, Émile Hirsch, his collaborator on previous restoration operations, was commissioned for the stained-glass windows. In 1884, the parisian glazier delivered four windows with historical subjects related to the institution, which took place in the two stairways, and in 1888 an allegorical stained-glass for the main hall, now removed. Laisné intended to complete the decoration of this hall with eight new windows, representating animals in their natural surroundings. Designed in 1889 by Albert Besnard, the painter who decorated the walls of this room, they were in fact not executed. But two of them were realized later by Henri Carot for private commissioners.